2012
DOI: 10.1053/j.semss.2011.11.011
|View full text |Cite
|
Sign up to set email alerts
|

The Latest Lessons Learned from Retrieval Analyses of Ultra-High Molecular Weight Polyethylene, Metal-on-Metal, and Alternative Bearing Total Disc Replacements

Abstract: Knowledge regarding the in vivo performance and periposthetic tissue response of cervical and lumbar total disc replacements (TDRs) continues to expand. This review addresses the following four main questions: 1) What are the latest lessons learned from polyethylene in large joints and how are they relevant to current TDRs? 2) What are the latest lessons learned regarding adverse local tissue reactions from metal-on-metal, CoCr bearings in large joints and how are they relevant to current TDRs? 3) What advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 42 publications
0
33
0
2
Order By: Relevance
“…The exact contribution of hemosiderin to revision remains unclear; however, a previous study has associated the deposition with the accumulation of activated macrophages that are positive for osteoclastic cell markers [25]. Although the amount of UHMWPE wear debris in the spine may not be severe enough to directly contribute to osteolysis [18], vertebral osteolysis was noted as a clinical complication in two patients with fixed-bearing L-TDRs, both of whom had tissues containing hemosiderin. The effect of hemosiderin in these tissues on UHMWPE wear-induced inflammation requires further investigation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The exact contribution of hemosiderin to revision remains unclear; however, a previous study has associated the deposition with the accumulation of activated macrophages that are positive for osteoclastic cell markers [25]. Although the amount of UHMWPE wear debris in the spine may not be severe enough to directly contribute to osteolysis [18], vertebral osteolysis was noted as a clinical complication in two patients with fixed-bearing L-TDRs, both of whom had tissues containing hemosiderin. The effect of hemosiderin in these tissues on UHMWPE wear-induced inflammation requires further investigation.…”
Section: Discussionmentioning
confidence: 90%
“…As a result of the decreased sliding distance in metal-on-polyethylene (MoP) L-TDRs compared with THA and TKA, wear and osteolysis of L-TDRs were originally thought to be negligible in the anterior column of the lumbar spine [21,22]. However, studies of historical L-TDRs with c-air-sterilized UHMWPE cores have demonstrated wear of the UHMWPE core along with several cases of osteolysis in the lumbar spine [18,35]. Additionally, both submicron (0.05-2 lm) and large UHMWPE wear particles (C 2 lm) were present in periprosthetic tissues from historical TDRs [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms leading to such reactions have been reported to be similar to those described after hip arthroplasty. 1,6,7 Only a few cases have been previously reported. 5 The severity of the clinical presentation makes the present case unique.…”
Section: Discussionmentioning
confidence: 99%
“…because the wear resistance of metal-on-metal articulation is superior to metal-on-polyethylene, the particulate debris generated by metal-on-metal couples is an order of magnitude less (but higher particle count) than that produced by metal-on-polymer couples. at this time, no adverse events relating to metal particulate debris or ion have been reported for the PRESTigE ® disc (Kurtz et al, 2012). a continuous monitoring of the in vivo biological effects of the metallic wear debris is required.…”
Section: Metal-on-metal Articulationmentioning
confidence: 94%